Exploring the short-term influence of a proprietary oil extract of black cumin (Nigella sativa) on non-restorative sleep: a randomized, double-blinded, placebo-controlled actigraphy study - Mohan, M. E.; Mohan, Mohind C.; Prabhakaran, Prathibha; Syam Das, S.; Krishnakumar, I. M.; Baby Chakrapani, P. S. (Frontiers in Nutrition, 2024)
Background: Nigella sativa (black cumin, or black seed) is popularly known as the seed of blessings in the Arab system of medicine. Though not widely recommended for sleep, a unique proprietary black cumin extract (BlaQmax®/ThymoDreamTM; BCO-5) has been shown to be helpful in the management of stress and sleep issues. Methods: This randomized, double-blind, placebo-controlled trial aimed to investigate the efficacy of BCO-5 on the sleep quality of volunteers characterized with a self-reported non-restorative sleep disorder. Healthy male and female participants (n = 70) aged 18-65 years with BMI ranging from 22-28 Kg/m2 were randomized to either placebo or BCO-5 (n = 35/group) and supplemented with 200 mg/day (soft gelatin capsules), half an hour before bedtime, for seven days. Actigraphy and a validated restorative sleep questionnaire (RSQ-W) were used to monitor the influence of BCO-5 on sleep. Results: Compared to placebo, BCO-5 significantly improved sleep quality, as evidenced by both intra-group and inter-group analyses of the actigraphy data. The relative improvements observed were sleep efficiency (7.8 %, P < 0.001), total sleep time (19.1 %, P < 0.001), sleep onset latency (35.4 %; P < 0.001), and wake-after-sleep-onset (22.5 %; P < 0.001) compared with placebo. BCO-5 also improved sleep by 75.3 % compared to baseline (P < 0.001) and by 68.9 % compared to placebo (P < 0.001), when monitored by RSQ-W. BCO-5 was well-tolerated with no reports of side effects or toxicity. Conclusion: BCO-5 significantly improved non-restorative sleep in seven days, indicating its potential role as a natural sleep aid.